Stabilitas dan Potensi Hasil Varietas Unggul Baru Padi Hibrida - Satoto, Satoto; Mejaya, Made Jana; Widyastuti, Y.; Rumanti, I. A. (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Nineteen field experiments were conducted in the provinces of West Java, Central Java, East Java, and Bali, during the 2008 dry season and the 2008/2009 wet season, to determine yield potential, yield stability, resistance to pests and diseases, and to evaluate the grain qualities of five introduced hybrid rice varieties and four hybrids from the Indonesian Center for Rice Research (ICRR). In each location, the experiment was arranged in a randomized block design with four replications, using 4 m x 5 m plot size. Observations were made on grain yields, yield components, plant resistant to major pests and diseases, and grain quality. The plant resistance to brown plant hopper (BPH), bacterial leaf blight (BLB), and tungro was evaluated at the glasshouse. Results showed that in some locations the hybrid rice yielded significantly higher than did inbred variety Ciherang, but it was inconsistence over locations. In the dry season, the average yields of hybrid rice were higher than those in the wet season. The average yield of two hybrids, namely MR1 and H30 over 19 locations was each significantly higher than that of Ciherang, however, the difference was not more than 9.6%. These two hybrids were found adaptive to all locations. Hybrid MR1 was resistant to BLB [Xanthomonas oryzae pv, oryzae (Xoo) patotipe III], whereas H30 was moderately resistant to Xoo pathotype III and BPH biotype 3. The amylose contents of MR1 and H30 was medium and the head rice percentages was >80%.